2020
DOI: 10.3390/su12031277
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Potential for Conservation and Farming in the Amazon and Cerrado under Four Policy Scenarios

Abstract: Since 2013, clearing rates have rapidly increased in the Amazon and Cerrado biomes. This acceleration has raised questions about the efficacy of current regional public and private conservation policies that seek to promote agricultural production while conserving remnants of natural vegetation. In this study, we assessed conservation and agricultural outcomes of four potential policy scenarios that represent perfect adherence to private sector, zero-deforestation commitments (i.e., the Amazon soy moratorium—A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
(106 reference statements)
1
15
0
Order By: Relevance
“…Previous research has shown that deforestation for soy is unnecessary in the Amazon due to the biome's large bank of suitable, cleared land (Gibbs et al, 2015;Brandão et al, 2020). Our results show that soy farms are an important source of these lands.…”
Section: Soy Properties and Regions Have Asm-compliant Land For Expansupporting
confidence: 48%
See 1 more Smart Citation
“…Previous research has shown that deforestation for soy is unnecessary in the Amazon due to the biome's large bank of suitable, cleared land (Gibbs et al, 2015;Brandão et al, 2020). Our results show that soy farms are an important source of these lands.…”
Section: Soy Properties and Regions Have Asm-compliant Land For Expansupporting
confidence: 48%
“…We overlaid Brazil's PRODES deforestation maps, a soy suitability map, and Landsat-based maps of soy extent with a database of publicly available property maps, which covered 78% of the total soy extent in 2019 (GLAD [Global Land Analysis and Discovery], 2019; INPE [Instituto Nacional de Pesquisas Espaciais], 2020). The soy suitability map, which was used to identify areas that are biophysically suitable for cropland expansion, was produced using the methods described in Brandão et al (2020) to merge a 30 × 30 m grid cell map of areas with and without restrictions for growing soy and a 60 × 60 m resolution map with integer values indicating degree of suitability (Soares-Filho et al, 2014;Rudorff and Oliveira, 2016). Property maps from three public sources were combined to produce a single map with public cadaster data from INCRA taking priority in the case of overlaps of boundaries between sources, followed by boundaries of those properties undergoing regularization in the Terra Legal program, and finally boundaries of properties in the Rural Environmental Registry (commonly known by its Portuguese-language acronym of CAR) (SFB [Serviço Florestal Brasileiro] (Freitas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Perobas Reserve is an integral protection area categorized for the use of natural resources (SNUC in Portuguese-Federal Law 9985/2000). However, Brazilian biodiversity is undergoing numerous attacks and misguided policies that aim to reduce protected areas (PA), with the argument of expanding agribusiness to improve the country's economic performance [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…SP for cattle ranching should address primarily the restoration of the productive potential of already existing degraded pastures (Cerri et al 2005, Montagnini 2008, Murgueitio et al 2011, Calle et al 2012, Montagnini et al 2013, Hohnwald et al 2015, Landholm et al 2019. In this perspective, Strassburg et al (2014) and Brandão et al (2020) estimated that increasing efficiency and productivity of Brazil's grasslands and pasturelands could cover the current production of meat, crops, wood products and biofuels until 2040, without further conversion of natural ecosystems. As indicated by our review, different types of SP are available to contribute to pasture improvement and restoration.…”
Section: Sp In Cattle Ranching and Soybean Cultivationmentioning
confidence: 99%
“…In fact, large farmers connected to global agribusiness are considered key players due to their scale of production; while in contrast, diversified systems of family farmers could have greater potential for sustainable development (Medina & Dos Santos 2017), but are hardly considered. Other limits reported are related to the fact that cattle are often raised on multiple properties prior to slaughter, fattened on noncompliant ranches, and then moved to a compliant property before sale to the slaughterhouses (so-called "laundering"), or even moved to regions not yet monitored by the agreements (so-called "leakage" - Gibbs et al 2016, Brandão et al 2020. This is mainly due to inadequate monitoring approaches and large segments of the cattle supply chain that are not tracked, meaning that such agreements do not necessarily translate into effective changes in sustainability (Buckley et al 2019).…”
Section: Public Policies and Supply Chain Initiativesmentioning
confidence: 99%